Relationship between Somatic Cell Counts, Mastitis and Milk Quality in Ettawah Grade and PESA Goats - PETLANE, Molefe; NOOR, Ronny Rachman; MAHESWARI, Rarah Ratih Adjie (Walailak Journal of Science and Technology (WJST), 2013)
Mastitis is a bacterial disease that leads to increased somatic cell counts and reduced milk quality in dairy goats. Reduction in quality is manifested through a reduction in fat, protein, lactose content and an increase in milk somatic cell counts and salts content. Thus mastitis affects productivity of animals and hence their economic value. The aim of this study was to analyze the effects of somatic cell counts (SCC) and mastitis on milk quality in PE and PESA. On-Farm mastitis tests were performed on 38 lactating dairy goats and milk samples were collected from both mastitis positive and healthy animals from which quality parameters were measured using a milko tester while bacterial isolation and enumeration were done following standard protocols. Data was analyzed descriptively and the results showed that somatic cell counts and somatic cell score correlate positively with mastitis (P < 0.05). Lactose and fat content decreased with severity of mastitis in both breeds whereas in PESA protein content increased with mastitis. Salt content increases with mastitis in both breeds. S. aureus was the most isolated bacteria and associated with high SCC whereas E. coli was poorly isolated. The study concludes that mastitis leads to increased SCC and reduced milk quality in dairy goats.